2019
DOI: 10.1016/j.radcr.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of fibrosing mesenteric tuberculosis

Abstract: This article presents fibrosing mesenteric tuberculosis in a 19-year-old Arab boy who presented with weight loss, fever, abdominal pain, and distension. Abdominal contrast enhanced computed tomography (CECT) was performed which showed large infiltrative ill-defined mesenteric-based enhancing soft tissue phlegmonous mass with surrounding desmoplastic reaction causing retraction-kinking of small bowel loops associated with central necrotic mesenteric lymph nodes, multifocal small bowel wall thickening, and ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis on the diagnostic accuracy of MRI in rectal cancer patients showed that the specificities of MRI for the T category and lymph node involvement were only 75% and 71% [ 27 ]. In a future study, diffusion-weighted imaging (DWI) may be considered for improved preoperative staging, due to the high accuracy in evaluating colorectal diseases [ 28 ] and especially for poor risk patients, computed tomography (CT) [ 29 ] and virtual CT colonoscopy [ 30 ] would be a better choice because they are noninvasive and less expensive with better spatial resolution in diagnosis of colorectal lesions. Lastly, although we confirmed the importance of chemotherapy in the neoadjuvant therapy in locally advanced rectal cancer patients, due to the retrospective nature of this study, it was difficult to confirm which chemotherapy regimen or cycle number would be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on the diagnostic accuracy of MRI in rectal cancer patients showed that the specificities of MRI for the T category and lymph node involvement were only 75% and 71% [ 27 ]. In a future study, diffusion-weighted imaging (DWI) may be considered for improved preoperative staging, due to the high accuracy in evaluating colorectal diseases [ 28 ] and especially for poor risk patients, computed tomography (CT) [ 29 ] and virtual CT colonoscopy [ 30 ] would be a better choice because they are noninvasive and less expensive with better spatial resolution in diagnosis of colorectal lesions. Lastly, although we confirmed the importance of chemotherapy in the neoadjuvant therapy in locally advanced rectal cancer patients, due to the retrospective nature of this study, it was difficult to confirm which chemotherapy regimen or cycle number would be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of the majority of TB cases in low and middle-income countries has established a relationship between the degree of advancement, basic infrastructure, quality of life in a nation , and efficiency of control measures for TB [ 3 ]. Indian scenario concerning tuberculosis is much worse, according to an estimate by whom India represented over 26% of the global TB burden [ 4 ]. Moreover, extrapulmonary TB (EPTB) which can be traced back to 1643 when the autopsy on Louis XIII showed ulcerative intestinal lesions associated with a large pulmonary cavity, the ever-growing incidence of the tubercular disease has seen a rise in cases of extrapulmonary TB [ 5 ].…”
Section: Introductionmentioning
confidence: 99%